Therapeutic potential of Lion's Mane (Hericium erinaceus) in neurological and cognitive disorders - a review of the literature - Tomasz Skubel; Julia Budzyńska; Jakub Czarnota; Michał Dobrzyński; Natalia Rybak; Iga Dudek (Kazimierz Wielki University, 2022)
Introduction: Hericium erinaceus is a medicinal and culinary mushroom that is widely present in the countries of East Asia. Bioactive compounds derived from the fruiting body or its mycelium have many properties, including: antioxidant, antidiabetic, anti-inflammatory, as well as hypolipidemic properties. It also has the potential to treat neurological disorders as it contains neurotrophic compounds that can cross the blood-brain barrier. Aim of the study: The aim of this work is to review scientific research on the potential properties of the H. erinaceus in treating diseases of the nervous system. Results: Many studies have shown that Hericium erinaceus can bring the desired effects as a complementary treatment and be an alternative in the treatment of depressive and cognitive disorders and, due to its strong neuroprotective nature, be used in Alzheimer's disease or in post-traumatic brain injury. Most of the cited studies concern experiments carried out on animal models. Conclusion: Due to the evidence of potentially neuroprotective properties of H. erinaceus, there is a need for further clinical trials in humans.